FE‐SEM observation of swelled seaweed using hydrophilic ionic liquid; 1‐butyl‐3‐methylimidazolium tetrafluoroborate. Issue 1 (16th October 2012) - Takahashi, Chisato; Shirai, Takashi; Fuji, Masayoshi
Abstract The method to observe the exact morphology of swelled seaweed as an example of biological material by field emission scanning electron microscopy (FE‐SEM) with the aid of hydrophilic ionic liquid (IL); 1‐butyl‐3‐methylimidazolium tetrafluoroborate is reported. Seaweed was first swelled in 3.5% NaCl solution and then treated with the IL and water mixture in 1:7 weight ratios and centrifuged to remove the excess IL solution. Thus treated seaweed maintained its morphology even at high magnification and did not show drying in the FE‐SEM chamber. This observation technique might be useful for various kinds of biological materials to be observed under FE‐SEM. Microsc. Res. Tech., 2013. © 2012 Wiley Periodicals, Inc.